Hidden Curriculum Pendidikan Agama Islam: Pendekatan Alternatif dalam Membentuk Karakter dan Budaya Religiusitas Siswa SMP Qurratul Uyun Trasak Larangan Pamekasan - Syaiful Anam; Mohammad Fahrur Rozi; Citra Siwi Hanayanti (Institut Kariman Wirayudha Sumenep, 2024)
This study aims to describe the Hidden Curriculum of Islamic Education as an alternative approach in shaping the character and religious culture of students at SMP Qurratul Uyun Trasak Larangan Pamekasan. The approach used in this research is descriptive-qualitative. Data sources were obtained through participatory interviews and observations, with informants including the School Principal, Vice Principal (Curriculum Vice Principal), Islamic Education Teachers (PAI), and students of SMP Qurratul Uyun. The results show that the implementation of the hidden curriculum activities of Islamic Education at SMP Qurratul Uyun Trasak Larangan Pamekasan in shaping the character and religious culture of students includes: Collective Morning Invocation and Prayer, Noon Prayer in Congregation, Friday Charity, Ramadan Lectures, Commemoration of Islamic Holidays, Habituation of S3 (Smile, Greet, Greet), Religious Studies, Visiting Sick Friends and Offering Condolences, and Quran Memorization. Factors inhibiting the implementation of hidden curriculum activities of Islamic Education at SMP Qurratul Uyun Trasak Larangan Pamekasan in shaping the character and religious culture of students include: Firstly, internal factors, namely the lack of awareness among some school residents about the importance of the Hidden Curriculum activities of Islamic Education at SMP Qurratul Uyun. Secondly, external factors, such as influences from outside the school environment and family. Thirdly, funding factors, specifically the limited budget available for hidden curriculum activities.